Nature's brain boosters: Exploring the potential of medicinal plants and natural compounds in neurosciences - Zahra Lorigooini (Shahrekord University of Medical Sciences, 2023)
As we all know, medicinal plants and natural compounds have been used for centuries in traditional medicine, and recent research has shed light on their potential for treating a wide range of neurological disorders. From Alzheimer's to Parkinson's to depression and anxiety, there is growing evidence that natural compounds can play a crucial role in promoting brain health and preventing or mitigating the effects of neurological disease. Over the last few decades, a growing interest has been in using natural compounds to treat neurological disorders. This is partly due to traditional pharmaceuticals' limitations and side effects and partially because research has shown that many natural compounds have potent neuroprotective and neuroregenerative properties. One example of a natural compound extensively studied for its potential in treating neurological disorders is curcumin, the active ingredient in turmeric. Curcumin has been shown to have anti-inflammatory and antioxidant properties and has been studied for its potential in treating Alzheimer's, Parkinson's, depression, and other neurological conditions. Other examples of natural compounds that have been studied for their potential in treating neurological disorders include resveratrol (found in red wine), omega-3 fatty acids (found in fish oil), and cannabidiol (found in cannabis).